Happiness in Latin America College Students: A Systematic Review - Rojas-Solís, José Luis (Consorcio de Universidades Mexicanas A.C., 2022)
The aim of this research is to analyze the main methodological characteristics of the existing scientific evidence on happiness in university students in Latin America; as well as the main findings and their associated factors. Following the PRISMA model, an exploratory systematic review of scientific investigations identified in five databases and published between 2000 and 2019 is presented. A total of 362 publications were obtained, of which fifteen were included in the final analysis of this review, highlighting the predominance of the quantitative approach, non-experimental studies, and the correlation between happiness and optimism. The results are discussed, emphasizing the methodological need for experimental studies, probabilistic samples that include more men, as well as the relevance of reporting ethical guidelines in each research. Regarding the general findings, the contribution of social relationships and optimism in the perception of happiness stands out, which would explain the high levels of happiness in Latin American university students. The need for more research in the region that contribute to strengthening the theoretical and empirical literature on the subject was pointed out.